AKIBAT HUKUM ATAS PEMBEBANAN HAK TANGGUNGAN YANG DIBATALKAN OLEH PUTUSAN PENGADILAN NOMOR 226/PDT.G/2022/PN SKT: Legal Consequences Of The Charge Of Mortgage Rights Cancelled By Court Decision Number 226/PDT.G/2022/PN SKT - Fauzia Rahmitha Sari; Dinda Keumala (Reformasi Hukum Trisakti, 2025)
This research is based on court decision No. 226/Pdt.G/2022/PN Skt. The objective of this study is to analyze the legal consequences of the cancellation of mortgage rights from a legal perspective by addressing the research problem: what are the legal consequences of the cancellation of mortgage rights imposed by court decision No. 226/Pdt.G/2022/PN Skt. This study utilizes secondary data, consisting of primary and secondary legal materials, and adopts a normative juridical approach to take a descriptive perspective in its research. The research is conducted through library studies, and the data is analyzed qualitatively, with conclusions drawn deductively. According to the research findings, several parties are affected by the legal consequences of the cancellation of mortgage rights imposed by the court decision, such as creditors losing their position as preferential creditors.